Patient-reported outcome claims in European and United States orphan drug approvals. Issue 1 (1st January 2018) - Jarosławski, Szymon; Auquier, Pascal; Borissov, Borislav; Dussart, Claude; Toumi, Mondher
ABSTRACT: Purpose: We aimed to evaluate the rate of usage and the kind of patient-reported outcome (PRO) claims in orphan drug approvals from the European Medicines Agency (EMA) dated between 1/1/2012 and 31/12/2016 and to compare them to those from the US Food and Drug Administration (FDA). Methods: Orphan drug approval documentation was obtained from the EMA website. PRO-related language was extracted from the Summaries of Product Characteristics (SmPCs). Data were compared to a previously published analysis of the FDA approvals from the same time period. Results: Out of 60 approvals that met the inclusion criteria, 12 products approved by the EMA for 13 (21.7%) orphan indications contained PRO language in the Clinical Studies section of the SmPC. Twelve SmPCs contained PRO instruments based on symptoms, five of which also concerned patient functioning. Eight approvals included PRO claims related to quality of life (QoL) most commonly in cancer treatment. Conclusion: The rate of PRO claims was lower for orphan drugs specifically than for all drug approvals by the EMA. However, in accordance with previous findings, the EMA appeared more inclined to grant PRO claims including health-related QoL than the FDA.